Réponses

2014-02-08T18:22:23+01:00
Bonsoir

3x -7x = -12 -2
-4x = -14
x = 14/4 = 7/2

-2x -4x = 26 -8
-6x = 18
x = -3

14x - 35 -3x = 4 +8x +1
14x -3x -8x = 4 +1 +35
3x = 40
x = 40/3

4 -3x +5 = -12x +8
-3x +12x = 8 -5-4
9x = -1
x = -1/9

(x+8)(9-x ) = .0
soit x +8 = 0 et x = -8
soit 9 -x = 0 et x = -9

(5x-7)(1-4x) = 0
soit 5x-7 = 0 donc 5x = 7 et x = 7/5
soit 1-4x = 0 donc -4x = -1 et x = 1/4


A = 4x -x² -12 +3x + x -2x² -3 +6x
-3x²  + 14x  -15

(x-3)(4-x + 1-2x)
(x-3)( -3x +5)

soit x -3 = 0 et x = 3
soit -3x +5 = 0 donc -3x = -5 et x = -5/3

- Longueur AE = 6 -x
- Aire ADE =( 6 ( 6-x))/2 =( 36 - 6x )/2 = 18 - 3x

18 -3x = 3(18 -3x)
18 -3x = 54 - 9x
-3x +9x = 54 -18
6x = 36
x = 6
Tableur, je ne peux pas